PEKERJA PEREMPUAN DI TAMBANG: BENTUK NEGOSIASI KESETARAAN GENDER DALAM DUNIA KERJA MASKULIN - Zulfatun Mahmudah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
Mine–which is always described as a hard and risky workplace–cannot be separated from gender issues. On the other hand, currently many women are able to work in the mine, and even they have very good work performance. This research is intended to explore how they adapt and interpret their work, and how they undergo a dual role as workers and housewives. This research was conducted using qualitative approach with phenomenological research method, in-depth interviews as a form of dialectical interaction. Respondents are woman coal mining operators at PT Kaltim Prima Coal (KPC), an international scale coal mine located in East Kalimantan. The informants are women who operate heavy equipment in the mine. The result shows that women arevable to adapt to the workplace where they were involved in, without seeing physical differences between men and women. They are able to play a dual role as workers and housewives. It can be concluded that in the mine women are able to adapt the work situation and condition without boundary that mine is the masculine workplace. It corrects various opinions, that women are people who are marginalized by the presence of mines.